Penatalaksanaan Fisioterapi Pada Kondisi Spondilosis Lumbal Di Rsud Moewardi Surakarta - Raharjo, Gusti Rahmat; , Totok Budi Santoso, SST.FT, MPH (2017)
Background: spondylosis lumbar disc is a condition found degeneration progressive discus invertebra that lead to changes in vertebral bone and ligaments, narrowing foramen invertebra from the front for crease ligamment posterior or as osteophytes, while from the rear because of the folds of ligament flavum, disc degeneration will stimulate the formation of osteophytes, which together with a swelling / thickening of soft tissue pressing medula spinal or spinal cord. Objective: To investigate the treatment of physiotherapy to reduce pain, improve muscle strength, increase range of motion and improve functional ability Methods: This paper uses the case study method for the management therapy 6 times Results: After therapy six times showed a reduction in tenderness T1: 4 to T6: 3 pain motion T1: 4 to T6: 3, increased range of motion of flexion T1: 46 into T6: 48, extension T1: 43menjadi T6: 42, side flexion right-T1: 39 to T6: 37, side flexion left T1: 39 to T6: 38, increasing the strength of the flexor muscles T1: 3 to T6: 4, extensor T1: 3 to T6: 4, the activity of functional capabilities 55% to 52% Conclusions: TENS and exercise therapy can reduce pain, increase range of motion, increase muscle strength and improve functional ability.